2006
DOI: 10.1002/elps.200600132
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the composition of recombinant human erythropoietin mixtures using capillary electrophoresis and multivariate calibration methods

Abstract: Estimation of the composition of recombinant human erythropoietin mixtures using capillary electrophoresis and multivariate calibration methods A multivariate calibration method using partial least-squares (PLS) is proposed in order to characterize binary mixtures of two types of recombinant human erythropoietin (epoetin alpha and beta), based on the analysis of the highly overlapped UV-electrophoretic profiles obtained with the CE methodology recommended by the European Pharmacopoeia (EurPh). A two-factor PLS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In summary, two trends can be found in literature: (1) Sialoform separation seems to be best accomplished close to the pI of the glycoprotein of interest and can then be applied to determine charge heterogeneity using UV detection, nice examples are given in [116,121]. (2) Sialoform and (partial) glycoform (of like charge) separation relies on strongly acidic conditions for most glycoproteins.…”
Section: Resolution and Information Achieved For Intact Glycoproteinsmentioning
confidence: 96%
See 1 more Smart Citation
“…In summary, two trends can be found in literature: (1) Sialoform separation seems to be best accomplished close to the pI of the glycoprotein of interest and can then be applied to determine charge heterogeneity using UV detection, nice examples are given in [116,121]. (2) Sialoform and (partial) glycoform (of like charge) separation relies on strongly acidic conditions for most glycoproteins.…”
Section: Resolution and Information Achieved For Intact Glycoproteinsmentioning
confidence: 96%
“…Applications of intact glycoprotein analysis are comprehensively summarized in [135]. Examples for a broad range of applications are: the determination of protein stability [116], the assessment of the charge heterogeneity of a recombinant protein within quality control [116], the observation of glycosylation changes due to host cell or growth media changes [116], the quantitative comparison between EPO alpha and beta in binary mixtures using PLS [121].…”
Section: Summary and Applicationsmentioning
confidence: 99%
“…Recently, commercially available polymers (EOTrol and UltraTrol) from Target Discovery (Palo, CA, USA) have been introduced [43] and provided glycoform profiling of erythropoietin [44,45], fetuin or a-acid glycoprotein [46]. Alkylamines as BGE additives have been reported not only to prevent protein adsorption by ion association with the negative charges on the capillary surface [47][48][49], but also to improve the glycoform resolution [50][51][52]. Combination of alkylamine and borate buffer, which is well known to promote glycoform separation through its interaction with sugars, is also a successful strategy [53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, the methods traditionally used for the analysis of MS data may be excessively time consuming. Chemometrics-assisted multiway data analysis is an excellent alternative for handling these complex data sets [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Using three-way data, determinations in the presence of unknown interferences are possible, when the instrumental signals are separated mathematically by achieving the second-order advantage [11]. We have recently demonstrated that a first-order multivariate calibration method with partial least squares (PLS) can be used to characterize mixtures of different erythropoietin samples based on the analysis of the electrophoretic separations of their glycoforms at a single wavelength [12]. However, the use of second-order CE-DAD data for multiway analysis of individual protein isoforms is precluded because the UV spectra of the comigrating isoforms are indistinguishable from each other.…”
Section: Introductionmentioning
confidence: 99%